Targeting the Tumor Microenvironment: An Unexplored Strategy for Mutant KRAS Tumors - Dias Carvalho, Patrícia (2020)
Current evidence strongly suggests that cancer cells depend on the microenvironment in order to thrive. In fact, signals from the surrounding tumor microenvironment are crucial for cancer cells´ aggressiveness, altering their expression profile and favoring their metastatic potential. As such, targeting the tumor microenvironment to impair cancer progression became an attractive therapeutic option. Interestingly, it has been shown that oncogenic KRAS signaling promotes a pro-tumorigenic microenvironment, and the associated crosstalk alters the expression profile of cancer cells. These findings award KRAS a key role in controlling the interactions between cancer cells and the microenvironment, granting cancer a poor prognosis. Given the lack of effective approaches to target KRAS itself or its downstream effectors in the clinic, exploring such interactions may open new perspectives on possible therapeutic strategies to hinder mutant KRAS tumors. This review highlights those communications and their implications for the development of effective therapies or to provide insights regarding response to existing regimens.